Awareness, Knowledge, Attitude, and Source of Information on HIV Infection Among College Students - Zheng C; Tang Q; Zeng J; Zhong H; Xie H; Ou H (Risk Management and Healthcare Policy, 2025)
Caixia Zheng,1,* Qingyun Tang,2,* Jianyong Zeng,1 Huiqun Zhong,2 Hongyan Xie,3 Hongjie Ou1 1Department of Infectious Diseases, First Affiliated Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 2Department of Infectious Diseases, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of General Practice, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongjie Ou, Department of Infectious diseases, The First Affiliated Hospital of Xiamen University, No. 10, Shanggu Road, Siming District, Xiamen City, 361003, Fujian Province, People’s Republic of China, Email ouhongjie@sina.com Hongyan Xie, Department of General Practice, Nanfang Hospital, Southern Medical University, No. 1838 Guangzhou Avenue North, Guangzhou City, 510515, Guangdong Province, People’s Republic of China, Email 492577598@qq.comObjective: To evaluate the college students’ awareness, knowledge, attitude, and source of information on human immunodeficiency virus (HIV).Methods: This is a multicenter study with 490 college students participated in the questionnaire survey. Among them, 261 are medical students and 229 are non-medical students. A questionnaire was used to collect socio-demographic data and investigate the awareness of and knowledge about HIV infection, the practice of preventive measures, and sources of HIV-related information.Results: There is no significantly different on self-report awareness of HIV infection between medical and non-medical students (P = 0.919). However, a higher proportion of non-medical students misunderstand the HIV transmission routes. For the sources of knowledge, non-medical students were more likely to obtain from the Internet (P=0.029), TV medias (P=0.027) and others (P=0.032). The proportion of medical students acquiring HIV-related knowledge from doctors was significantly higher (P< 0.001). A higher percentage of non-medical students indicated a lack of HIV knowledge and expressed a need for more HIV related education (P=0.002). Non-medical students expressed a preference for HIV education that covers a broader spectrum of HIV-related knowledge (P=0.046), indicating a desire for more comprehensive understanding beyond basic HIV-related awareness. In contrast, medical students indicated a preference for more frequent sessions with longer durations (P=0.038).Conclusion: Medical students were significantly more aware of HIV related knowledge than the non-medical students. Our research can provide relevant data support for further improving the methods and content of health education for young people.Keywords: acquired immunodeficiency syndrome, human immunodeficiency virus, awareness, knowledge, attitude, source